ASSOCIAR AS CASAS FAMILIARES RURAIS À DIFUSÃO DAS TÉCNICAS NA AMAZÔNIA BRASILEIRA - Sablayrolles, Philippe; Flohic, Alphonse; Reis, Serginando (Cadernos de Ciência & Tecnologia, 2005)
Neste artigo, foi analisada a atuação, no programa de difusão de técnicas, de três atores principais associados aos agricultores-experimentadores, a saber: as associações de agricultores gerenciadoras das Casas Familiares Rurais (CFRs), a ONG de apoio Laet (Laboratório Agroecológico da Transamazônica) e a pesquisa agronômica (Embrapa). No programa, foram utilizadas ferramentas simples para acompanhamento dos agricultores, da evolução da rede de agricultores-experimentadores e dos métodos de apoio à difusão das técnicas. Por esse enfoque, foi possível uma contínua discussão - entre agricultores/e agentes de apoio - dos temas prioritários de inovação, da escolha das práticas a serem testadas ou difundidas e sua adaptação. Foram analisados alguns resultados de difusão com a intenção de avaliar o potencial da proposta.Termos para indexação: economia e desenvolvimento rural, difusão de tecnologia, metodologias participativas. ASSOCIATING CASAS FAMILIARES RURAIS WITH EXTENSION ACTIVITIES (BRAZILIAN AMAZON) ABSTRACT This paper presents a specific method for agricultural extension work, that is, for the adoption and dissemination of agricultural techniques, in the Brazilian Amazon frontier regions. The deficiency in technical references and the weakness of extension practice from the public institutions in these regions led to the development of this extension program with local farmers' organisations. The Laboratório Agroecológico da Transamazônica (Laet), associated with a public research institution (Embrapa Amazônia Oriental) and a public university (Universidade Federal do Pará, UFPa), bases its action on a permanent partnership with a network of individual farmers and with local rural schools (Casas Familiares Rurais, CFR) interested in local sustainable development. Laet's extension activities are organised in four levels of intervention, each intensified through the CFR partnerships. The first level, from the historical and functional point of view, is relationships with individual farmers, established through experiments with technical alternatives and management advising. The second is the administration of a network of "farmer-researchers" to increase the social and technical representativeness of the program. The third involves the dissemination of techniques in partnership with the farmers, the farmer-research network and farmers' organisations. The fourth is a partnership with local and regional institutions for dissemination of agricultural methods: the university, local extension institutions, and activities in other regions. Relatively simple and unobtrusive tools for monitoring are preferred. The farm families record management and experiments; evaluation and advice are based directly on those records, without further data formalisation. This approach allows a permanent discussion between farmers, farmers' organisation, CFRs, and Laet about priorities in the innovations for experimentation, adaptation and dissemination.Index terms: economy and rural development, tools and methods. ASSOCIER LES MAISONS FAMILIALES RURALES À LA DIFFUSION DES TECHNIQUES (AMAZONIE BRÉSILIENNE) RÉSUMÉ Dans ce programme d'adaptation et de diffusion de techniques, trois acteurs principaux sont associés aux paysans-expérimentateurs: les Maisons Familiales Rurales (MFR), associations paysannes; l'ONG d'appui Laet (Laboratoire Agroécologique de la Transamazonienne); la recherche agronomique (Embrapa). Des outils légers sont privilégiés pour le suivi d'exploitation, l'évolution du réseau de paysans, les méthodes d'appui à la diffusion de techniques. Cette approche permet une élaboration commune paysans/agents de l'appui des thèmes prioritaires d'innovation, du choix des pratiques à tester ou à diffuser et de leur adaptation. On examine quelques résultats de cette diffusion, de façon à illustrer le potentiel que représente un tel montage.Termes d'indexation: économie et développement rural, méthodes et outils.
Keywords: economia e desenvolvimento rural; difusão de tecnologia; metodologias participativas